Dielectrophoretic characterization of dendritic cell deformability upon maturation - Anoop Menachery; Jiranuwat Sapudom; Abhishek Vembadi; Aseel Alatoom; Jeremy Teo; Mohammad A Qasaimeh (BioTechniques, 2021)
We have developed a rapid technique for characterizing the biomechanical properties of dendritic cells using dielectrophoretic forces. It is widely recognized that maturing of dendritic cells modulates their stiffness and migration capabilities, which results in T-cell activation triggering the adaptive immune response. Therefore it is important to develop techniques for mechanophenotyping of immature and mature dendritic cells. The technique reported here utilizes nonuniform electric fields to exert a substantial force on the cells to induce cellular elongation for optical measurements. In addition, a large array of interdigitated electrodes allows multiple cells to be stretched simultaneously. Our results indicate a direct correlation between F-actin activity and deformability observed in dendritic cells, determined through mean fluorescence signal intensity of phalloidin.